Aluminum acceptor activation and charge compensation in implanted p-type 4H-SiC - Weiße, Julietta; Hauck, Martin; Krieger, Michael; Bauer, Anton; Erlbacher, Tobias (AIP Advances, 2019)
In 4H silicon carbide, aluminum implantation causes unusual high compensation ratios as obtained from Hall effect investigations by fitting the neutrality equation with a single acceptor. We show that this approach cannot fully describe the experimental data, in particular in case of moderate doping and at high measurement temperatures above 450 K. We develop two extended models by adding an additional acceptor- or donor-like defect to the equation. Both approaches describe the data well. However, it turns out that an additional aluminum-correlated acceptor is the more reasonable choice. In this case, the compensation ratio stays almost independent of the implantation dose between 30 % and 40 %. The deep acceptor is located at EV + (280...400) me
Keywords: silicon carbide; SiC; aluminum implantation; charge compensation

An adapted method for analyzing 4H silicon carbide metal-oxide-semiconductor field-effect transistors - Hauck, Martin; Lehmeyer, Johannes; Pobegen, Gregor; Weber, Heiko B.; Krieger, Michael (Communications Physics, 2019)
Silicon carbide (SiC) metal-oxide-semiconductor field-effect transistors (MOSFETs) are key devices for next-generation power electronics. However, accurate determination of device parameters from 3-terminal characteristics is hampered by the presence of interface traps. Here we present a method that, in contrast to previous evaluation schemes, explicitly considers those defects. A well-tractable parametrization of the SiC/SiO2-specific interface trap spectrum is introduced that reflects the body of known data. With this ingredient, we develop an analysis that targets for an accurate determination of device parameters from simple 3-terminal characteristics. For its validation, we investigate MOSFETs with significantly different defect densities. The resulting parameters – charge carrier density, mobility and threshold voltage – are in excellent agreement with Hall effect investigations on the very same devices, avoiding systematic errors inherent to conventional evaluation techniques. With this adapted scheme, 4H-SiC power MOSFETs, even packaged, can be meaningfully characterized, speeding up innovation cycles in energy-saving power electronics.<br
Keywords: silicon carbide; SiC; power electronic transistors; interface defects

Analysis of Compensation Effects in Aluminum-Implanted 4H-SiC Devices - Weiße, Julietta; Hauck, Martin; Sledziewski, Tomasz; Tschiesche, Mattias; Krieger, Michael; Bauer, Anton; Mitlehner, Heinz; Frey, Lothar; Erlbacher, Tobias (Materials Science Forum, 2018)
In this work, we analyze compensating defects which are formed after implantation of aluminum (Al) into n-type 4H-SiC epitaxial layers and subsequent thermal annealing. These defects reduce the expected free charge carrier density by 84% for a low doped layer with [Al]impl ≈ 9·1016 cm-3 and by 27 % for a high doped layer with [Al]impl ≈ 2·1019 cm-3. Furthermore, an electrical activation ratio of implanted aluminum ions of 100 % is calculated. The ionization energy of implanted aluminum as measured by Hall effect and admittance spectroscopy ranges from 101 meV to 305 meV depending on the doping concentratio
Keywords: Activation; Admittance Spectroscopy; Aluminium Implantation; Compensation; Hall Effect; Ionization Energy; Secondary Ion Mass Spectrometry (SIMS)

Attosecond-fast internal photoemission - Heide, Christian; Hauck, Martin; Higuchi, Takuya; Ristein, Jürgen; Ley, Lothar; Weber, Heiko B.; Hommelhoff, Peter (Nature Photonics, 2020)
The photoelectric effect has a sister process relevant in optoelectronics called internal photoemission1,2,3. Here an electron is photoemitted from a metal into a semiconductor4,<a title="Di Bartolomeo, A. Graphene Schottky diodes: an experimental review of the rectifying graphene/semiconductor heterojunction. Phys. Rep. 606, 1–58 (2016)." href="https://www.nature.com/articles/s41566-019-0580-6#ref-CR5">5. While the photoelectric effect takes place within less than 100 attoseconds (1 as = 10−18 seconds)6,7, the attosecond timescale has so far not been measured for internal photoemission. Based on the new method CHArge transfer time MEasurement via Laser pulse duration-dependent saturation fluEnce determinatiON—CHAMELEON—we show that the atomically thin semimetal graphene coupled to bulk silicon carbide, forming a Schottky junction, allows charge transfer times as fast as (300 ± 200) as. These results are supported by a simple quantum mechanical model simulation. With the obtained cut-off bandwidth of 3.3 PHz (1 PHz = 1015 Hz) for the charge transfer rate, this semimetal/semiconductor interface represents a functional solid-state interface offering the speed and design space required for future light-wave signal processing.<br
Keywords: Nonlinear optics; Optical properties and devices; Optoelectronic devices and components; Ultrafast photonics

On the origin of charge compensation in aluminum-implanted n-type 4H-SiC by analysis of hall effect measurements - Weiße, Julietta; Hauck, Martin; Sledziewski, Tomasz; Krieger, Michael; Bauer, Anton; Mitlehner, Heinz; Frey, Lothar; Erlbacher, Tobias (Materials Science Forum, 2019)
Aluminum implanted 4H-SiC often shows an unexpected increase of the free hole density at elevated temperatures in Hall Effect measurements. Here, we exhibit that this phenomenon cannot solely be traced down to the Hall scattering factor and the presence of excited acceptor states. It is necessary to assume an additional defect center in the lower half of the band gap with ionization energies higher than that of aluminum to explain this behavior. Therefore, we investigated ionimplanted square van-der-Pauw samples with Hall Effect and complementary SIMS measurements. An analysis of the data using the neutrality equation reveals compensation ratios of 20 % to 90 %, depending on the aluminum concentration and the concentration of the deep defect center of up to 50 % of the doping.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Activation; Aluminum implantation; Compensation; Hall Effect; High temperature implantation; Ionization energy

On the origin of drain current transients and subthreshold sweep hysteresis in 4H-SiC MOSFETs - Rasinger, Fabian; Hauck, Martin; Rescher, Gerald; Aichinger, Thomas; Weber, Heiko B.; Krieger, Michael; Pobegen, Gregor (Applied Physics Letters, 2019)

On the origin of threshold voltage instability under operating conditions of 4H-SiC n-channel MOSFETs - Pobegen, Gregor; Weiße, Julietta; Hauck, Martin; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2016)

Persistent Conductivity in n-type 3C-SiC Observed at Low Temperatures - Beljakowa, Svetlana; Hauck, Martin; Bockstedte, Michel Georg; Fromm, Felix; Hundhausen, Martin; Nagasawa, H.; Weber, Heiko B.; Pensl, Gerhard; Krieger, Michael (Materials Science Forum, 2014)
Persistent conductivity in n-type 3C-SiC is investigated in a wide temperature range down to 3 K by Hall effect, admittance spectroscopy, low temperature photoluminescence (LTPL) and Raman spectroscopy. We propose a model, which clearly explains the persistent behavior of the electron density η below 50 K. It is experimentally verified that the persistent conductivity results from doped SF bunches, which can be considered nano-polytype inclusions in 3C-SiC. © (2014) Trans Tech Publications, Switzerland.
UnivIS-Import:2015-04-14:Pub.2014.nat.dphy.IAP.LAP.persis
Keywords: 3C-SiC; Hall effect; Persistent conductivity; Raman spectroscopy; Stacking faults (SFs)

Präziser Einblick ins Innerste von Siliziumkarbid-MOSFETs - Hauck, Martin; Krieger, Michael (Elektronikpraxis - Profiline, 2019)
Keywords: Siliziumkarbid; SiC; MOSFET; Grenzflächendefekte; Near-Interface-Traps; NITs

Publisher's Note: Aluminum acceptor activation and charge compensation in implanted p-type 4H-SiC (AIP Advances (2019) 9 (055308) DOI: 10.1063/1.5096440) - Weiße, Julietta; Hauck, Martin; Krieger, Michael; Bauer, A. J.; Erlbacher, T. (AIP Advances, 2019)
This article was originally published online on 9 May 2019. Due to a production error, the last sentence of the abstract and the second paragraph, second sentence of the conclusions appeared incorrectly. AIP Publishing apologizes for this error. All online versions of the article were corrected on 16 May 2019.
CRIS-Team Scopus Importer:2019-07-23

Quantitative Investigation of Near Interface Traps in 4H-SiC MOSFETs via Drain Current Deep Level Transient Spectroscopy - Hauck, Martin; Weiße, Julietta; Lehmeyer, Johannes; Pobegen, Gregor; Weber, Heiko B.; Krieger, Michael (Materials Science Forum, 2016)
Keywords: MOSFET; drain current DLTS; Hall effect in MOS channel; interface traps; NITs; POA

Structural fluctuations cause spin-split states in tetragonal (CH₃NH₃)PbI₃ as evidenced by the circular photogalvanic effect - Niesner, Daniel; Hauck, Martin; Shrestha, Shreetu; Levchuk, Ievgen; Matt, Gebhard; Osvet, Andres; Batentschuk, Miroslaw; Brabec, Christoph; Weber, Heiko B.; Fauster, Thomas (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Lead halide perovskites are used in thin-film solar cells, which owe their high efficiency to the long lifetimes of photocarriers. Various calculations find that a dynamical Rashba effect could significantly contribute to these long lifetimes. This effect is predicted to cause a spin splitting of the electronic bands of inversion-symmetric crystalline materials at finite temperatures, resulting in a slightly indirect band gap. Direct experimental evidence of the existence or the strength of the spin splitting is lacking. Here, we resonantly excite photocurrents in single crystalline (CH3NH3)PbI3 with circularly polarized light to clarify the existence of spin splittings in the band structure. We observe a circular photogalvanic effect, i.e., the photocurrent depends on the light helicity, in both orthorhombic and tetragonal (CH3NH3)PbI3. At room temperature, the effect peaks for excitation photon energies ΔE=110 meV below the direct optical band gap. Temperature-dependent measurements reveal a sign change of the effect at the orthorhombic extendashtetragonal phase transition, indicating different microscopic origins in the two phases. Within the tetragonal phase, both ΔE and the amplitude of the circular photogalvanic effect increase with temperature. Our findings support a dynamical Rashba effect in this phase, i.e., a spin splitting caused by thermally induced structural fluctuations which break inversion symmetr
Keywords: organic–inorganic perovskite; lead halide perovskite; circular photogalvanic effect; dynamical Rashba; Rashba effect